APPLICATION OF LIFE CYCLE COST ANALYSIS (LCCA) IN SELECTING ALTERNATIVE PROGRAMS TO REDUCE DERATING (CASE STUDY OF PLTU NAGAN RAYA) - Dwi Prabowo, Yulianto
PLTU Nagan Raya is a steam power plant with 2 x 110 MW installed capacity located in Aceh. As the biggest power plant in Aceh, PLTU Nagan Raya also have important role in Sumatera Utara electricity system. Recently, within derating condition, PLTU Nagan Raya requires improvement to maintain its optimal performance. The purpose of this study is to perform an economic analysis toward derating and forced outage’s improvement programs by applying life cycle cost analysis (LCCA).